European Neigbourhood Policy: key principles - Hasyak, Maryana (Видавництво Львівської політехніки, 2013)
The article considers the policy of the European Union towards neighboring states, including Ukraine; the review of the legal framework of the European Neighborhood Policy and its underlying principles has been done; the attitude of domestic scientists to such program of the EU and their prediction about its impact on the future of Ukraine in the global geopolitical space has been analized.
Keywords: the European Union; the European Neighbourhood Policy; European Neighbourhood and Partnership Instrument; Neighboring States; Member States; the Action Plan